Knee strength outcomes in adolescents by age and sex during late-stage rehabilitation after anterior cruciate ligament reconstruction. (September 2021) - Roman, Dylan P.; Ness, Brandon M.; Giampetruzzi, Nicholas; Cleland, Joshua A.; Weaver, Adam
Abstract: Objective: To determine if knee strength differences exist according to age group and sex among adolescents during late-stage anterior cruciate ligament reconstruction (ACLR) rehabilitation. Design: Retrospective cohort study. Methods: Consecutive patients who had undergone ACLR with a hamstring autograft completed isokinetic knee strength assessment. Patients were categorized into early (ages 11–14 years) and middle (ages 15–17 years) adolescence. A two-way MANOVA was used to examine strength differences according to age group and sex. Results: 144 patients were included in the analysis (56.9% females, age = 15.3 ± 1.5 years; days since surgery = 228.2 ± 41.2). Differences in quadriceps peak torque were identified between age groups on the involved (p = 0.001) and uninvolved limbs (p < 0.001), however, no differences in quadriceps peak torque were found between age groups when normalized to body mass (p = 0.16–0.49). Differences between groups according to sex were identified for each strength outcome (p < 0.01), with decreased normalized quadriceps (12–13%) and hamstring (13–16%) peak torque for females. No interactions between age group and sex were noted, F(8, 133) = 1.48, p = 0.17. Conclusion: Early adolescents produced less quadriceps and hamstring peak torque compared to middle adolescents after ACLR. No differences were found between age groups when normalized to body mass. Highlights: Knee strength outcomes were analyzed according to age and sex during late-stage ACLR rehabilitation in adolescents. Females had decreased normalized quadriceps (12–13%) and hamstring (13–16%) peak torque compared to males. Early adolescents produced less quadriceps and hamstring peak torque compared to middle adolescents. No strength differences were found between age groups when peak torque was normalized to body mass.